Measuring social norms and attitudes about age-disparate transactional sex: Psychometric testing of the NAATSS - Nancy A Perrin; Ruti G Levtov; Caroline Ferraz Ignacio; Luis Anunciação; Jesus Landeira-Fernandez; Linda Cerdeira; Giovanna Lauro; Beniamino Cislaghi; Ana Maria Buller (Elsevier, 2022)
Summary: Background: Transactional sex between girls under 18 years-old and adult men at least ten years older, known as age-disparate transactional sex (ADTS), is an established risk factor for HIV, STI and early pregnancy among girls and women. Social norms or beliefs about what others expect from you and what others do can sustain behaviours such as ADTS even when individuals may be personally against them. In order to evaluate interventions to change social norms, validated instruments for measuring change in personal beliefs and social norms regarding ADTS are needed. Methods: Items for the Norms and Attitudes on Age-Disparate Transactional Sex Scale (NAATSS) were generated based on qualitative interviews and expert panel review. The reliability and validity of the NAATSS was tested in a representative sample (N = 431) from Brazilian favelas. Factor analysis assessed construct validity, Cronbach's alpha assessed reliability, and t-tests and analysis of variances tested hypothesized differences between gender, age, and previous experience with ADTS in both the social norms and personal beliefs domains. Findings: Factor analysis revealed three factors in each domain. The factors were labelled "Attributions to Girls' Behaviour" which has 5 items, "Men's Motivations" with 5 items, and "Girls' Readiness to have Sex" with 3 items. The subscales evidenced acceptable reliability with Cronbach's alphas ranging from 0.72 to 0.83 for the social norms subscales and 0.59 to 0.82 for the personal beliefs subscales. Interpretation: The items were developed based on qualitative research and expert rankings and the resulting Norms and Attitudes on ADTS Scale exhibits strong psychometric properties. Each of the three subscales within the two domains illustrate good factor structure, acceptable internal consistency reliability, and are supported by the significance of the hypothesized group differences. Funding: This work was supported by the OAK Foundation [grant number OCAY-16-188].